PERAN AKTIF PEREMPUAN MUSLIM - Taufik Munir (MUWAZAH : jurnal kajian gender, 2014)
Issues on the Status of Women in Islam will always be a discourse which is always inviting pros and cons. Although in terms of women's rights has been codified in revelation and tradition of the Prophet (Hadith), but it turns out after him after the death, the condition of Muslim women considered to be undergoing drastic changes. The amendment relates to the concept of women's liberation, along with changes in the interpretation of the validity of the scholars of fiqh sources-formal legal about women's rights in Islam. The emergence of stigmatization in our society, that women do not need to play outside the home also play a role worsen climate of freedom for women.